2015
DOI: 10.1063/1.4922506
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of L1 FePt/Fe45Co55 thin films for rare earth free permanent magnet applications

Abstract: The magnetic properties of magnetron sputtered bilayers consisting of Fe45Co55 ultrathin layers on top of L10 FePt films epitaxially grown on MgO substrates are studied in view of their possible application as rare earth free permanent magnets. It is found that FePt layers induce a tetragonal distortion to the Fe-Co layers which leads to increased anisotropy. This allows to take advantage of the Fe-Co high magnetic moment with less significant loss of the coercivity compared to a typical hard/soft exchange spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…We use ab initio calculations to understand the atomic structure as well as magnetic anisotropy in such systems and focus on FePt/FeCo superlattices as thin films of FePt/Fe, FePt/Co, and FePt/FeCo have been realized 4,5 and a high value of 54 MGOe for the energy product has been obtained 11 for aligned and exchange-coupled FePt based films. Also a similar value of 50 MGOe has been obtained 5 for films with 5 monolayers (ML) of FeCo on 7 ML of FePt. 60 Pt 40 /Co bilayers.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…We use ab initio calculations to understand the atomic structure as well as magnetic anisotropy in such systems and focus on FePt/FeCo superlattices as thin films of FePt/Fe, FePt/Co, and FePt/FeCo have been realized 4,5 and a high value of 54 MGOe for the energy product has been obtained 11 for aligned and exchange-coupled FePt based films. Also a similar value of 50 MGOe has been obtained 5 for films with 5 monolayers (ML) of FeCo on 7 ML of FePt. 60 Pt 40 /Co bilayers.…”
Section: Introductionsupporting
confidence: 59%
“…A key figure of merit is the maximum energy product (BH) max = µ 0 M s 2 /4, where M s is the saturation magnetization and µ 0 is the permeability. RE based magnets SmCo 5 and Nd 2 Fe 14 B have a high energy product 2,3 of 31 MGOe and 50 MGOe, respectively but the value for RE free magnets is generally lower. Here we report from calculations a high value (up to ∼97 MGOe) of (BH) max for FePt/FeCo exchange coupled superlattices and show that the optimal thickness of the soft magnetic phase to achieve high magnetization as well as large magnetic anisotropy energy (MAE) is less than ∼2 nm.…”
Section: Introductionmentioning
confidence: 99%
“…FeCo is the best chosen soft ferromagnetic material to couple with FePt due to its high saturation magnetization of 2.4 T [23,24], low anisotropy ∼4 × 10 4 J m −3 [25,26] and high Curie temperature [27,28]. The exchange-coupled FePt/FeCo bilayer thin films are the most stimulating magnetic multilayers in terms of distinctive properties such as large saturation magnetization, high coercivity and hence a high energy product retaining a high thermal stability as well [29,30]. The switching field here is reduced by varying the thickness of FeCo layer.…”
Section: Introductionmentioning
confidence: 99%
“…2c . 61 These discoveries clearly show the potential applications of FeCo alloys in permanent magnets. In 2014, the interstitial boron doped FeCo, introduced by Khan and Hong, indicated that the magnetocrystalline anisotropy constant can reach 0.8 MJ m −3 with an estimated energy product of 100 MGOe.…”
Section: Preparation and Magnetic Properties Of Iron-based Ferrous Ma...mentioning
confidence: 93%